Pengaruh Model Kooperatipe Bamboo Dancing terhadap Keterampilan Menulis Eksposisi Siswa SMP - Hardani, Maisuri (GERAM: Gerakan Aktif Menulis, 2017)
The purpose of this study to describe the effect of the use of cooperative learning model Bamboo Dancing on learning outcomes writing text exposition seventh grade students of SMPN 4 Padang Panjang. The theory used in this study as follows. First, writing skills Text exposition. Second, cooperative learning model Bamboo Dancing.Jenis This study was a quantitative research with experimental method. The research was one group pretest and posttest design. Total population of 137 students with a sample of 24 students. The sample in this research is class VII. 4 SMPN 4 Padang Panajng determined using purposive sampling technique. In this research there are two variables, namely (1) the writing skills of students Subtitles exposition before using cooperative learning model Bamboo Dancing, and (2) the writing skills of students after the text exposition cooperative learning model Bamboo Dancing. Instruments used in this research is to test the performance. This research data is the writing skills test score results Subtitles exposition seventh grade students of SMPN 4 Padang Panjang before and after using cooperative learning model Bamboo Dancing. The results of this study are based on the t-test, the alternative hypothesis (H_1) received the 95% significance level and degrees of freedom (df) = (N_1 + n_2) -2 because thitung> t table (1.17> 1.98). In other words, the writing skills Text exposition seventh grade students of SMPN 4 Padang Panjang after using cooperative learning model is better than the Dancing Bamboo writing skills Text exposition seventh grade students of SMPN 4 Padang Panjang before using cooperative learning model Bamboo Dancing.